Pembelajaran Kooperatif Tipe Jigsaw dengan Pendekatan Pengajuan Masalah (Problem Posing) di Kelas VIII SMP Ittihad Makassar - Rusmin Madia; Muhammad Arif Tiro; Awi Dassa (IAIN Ambon, 2017)
This study is research and development refers to 4-D Thiagarajan model which aims at producing a valid learning devices and examining whether cooperative learning tools of jigsaw type problem posing giving approach is effektive to be applied on circle subject matter of grade VIII students at SMP Ittihad Makassar. This study is conducted due to low quality of education, teacher centered is still applied in school in mathematics learning, and a pleasant learning condition has not been achieved yet. Therefore, the problem statement related to the main problem is how is the implementation and the effectiveness of cooperative learning devices of jigsaw type through problem giving approach on circle subject matter. The devices of be produced in this study are the lesson plan, teacher’s manual, student’s book, student’s workbook, and lerning achievement test. Data on teacher and students’ activities were obtained by using observation sheet; whereas, to examine students’ learning achievement, test of learning achievement was employed. Data on students’ response was obtained by using questionaire. Data was analyzed by using statistics deskriptive analysis. The results show that (1) the students are active in having cooperative learning of jigsaw type through problem giving approach, (2) the teacher’s activity in cooperative learning of jigsaw type through problem giving approach giving is extremely good, (3) the students’ response on positive, and (4) the result of students’ learning achivement after having the cooperative learning of jigsaw type through problem giving approach has met the criteria of classical mastery. The result reveals that cooperative learning of jigsaw type through problem giving approach has conducted and is effective to be applied on circle subject matter of grade VIII-A students at SMP Ittihad Makassar. It is suggested that mathematics learning, particulary on the circle subject matter at SMP, teachers should use cooperative learning devices of jigsaw type through problem giving approach because students are delighted and interested in having cooperative learning of jigsaw type through problem giving approach. Key Word: cooperative learning, Problem posing